Effects of physical activity in patients with systemic lupus erythematosus: a narrative review - Kaczorowski, Wojciech; Wilkowska, Krystyna; Michałowski, Maciej; Sudomir, Maria; Knysak, Karol; Maj, Alicja; Szczerba, Mateusz; Hejnosz, Aleksandra; Jastrzębski, Michał; Piątek, Maja (Quality in Sport, 2026)
Systemic lupus erythematosus (SLE) is a chronic autoimmune disease characterised by heterogeneous clinical involvement and persistent symptom burden despite advances in pharmacological therapy. Fatigue, mood disturbances, reduced physical functioning and heightened cardiometabolic risk remain prevalent and only partially amenable to medication alone. Growing interest has therefore focused on the role of physical activity as a complementary strategy in SLE management. This narrative review synthesises evidence from interventional and observational studies exploring associations between physical activity, structured exercise and key clinical outcomes in adults with SLE. Individuals with SLE consistently demonstrate reduced habitual activity, lower fitness and increased sedentary time compared with the general population. Across multiple trials, aerobic, resistance and combined exercise programmes were safe in clinically stable disease and did not increase activity or flare rates. Exercise interventions improved functional capacity, fatigue and selected psychological outcomes, whereas observational studies additionally link higher activity levels to better mood, sleep and cognitive functioning. Physical activity and fitness also correlate with more favourable cardiometabolic profiles, including lower arterial stiffness and reduced markers of subclinical atherosclerosis. Mechanistic data suggest that exercise may attenuate inflammatory signalling and modulate immune pathways relevant to SLE. Overall, physical activity represents a safe and valuable adjunct to standard therapy, offering benefits across functional, symptomatic and cardiometabolic domains. Further high-quality trials are required to optimise exercise prescriptions and evaluate long-term effects in diverse SLE populations.